A Direct Test of Legislative Gatekeeping. Issue 4 (31st October 2020) - Thieme, Sebastian
Abstract : Tests of legislative gatekeeping theories have been hampered by the absence of status quo estimates, making these tests vulnerable to selection bias. I overcome this problem with a novel data set on positions by private interests in Iowa, Nebraska, and Wisconsin because these states' legislatures record organizations' positions on lobbied bills irrespective of whether the bills receive floor consideration. This permits an estimation of the ideological locations of status quo policies for bills with and without floor consideration and in turn rigorous empirical tests of agenda‐control theories. The data provide substantial evidence of partisan and nonpartisan gatekeeping and can adjudicate among the two models of gatekeeping in specific circumstances. In particular, they corroborate partisan gatekeeping in the Iowa House and the Wisconsin Assembly and cannot distinguish between the two accounts in the other chambers. Moreover, the results show that strong partisan institutions need not result in predominantly partisan gatekeeping.